Research on the synergy mechanism of Chinese liquor brand's overseas market entry mode and brand positioning (Journal of economic and management development research, 2025)
This paper takes the development of Chinese liquor brands in overseas markets as the research object, explores the cross-cultural marketing problems under the differences in wine culture, and discusses the synergy between market entry mode and brand positioning. Through theoretical analysis, comparative case studies, model construction, etc., this paper systematically sorts out the impact of different entry models on brand positioning and analyzes how the two jointly improve the success rate of overseas markets. The conclusion drawn from the research is that the effective matching of entry mode and brand positioning can improve resource allocation, strengthen brand adaptability, and provide theoretical support and practical guidance for the internationalization of Chinese liquor brands.
Keywords: Chinese liquor brands; Overseas market entry model; Brand positioning; Synergy mechanism